Three-dimensional organization of promyelocytic leukemia nuclear bodies - Lang, Marion Christine; Jegou, Thibaud; Chung, Inn; Richter, Karsten; Münch, Sandra; Udvarhelyi, Anikó; Cremer, Christoph; Hemmerich, Peter; Engelhardt, Johann; Hell, Stefan; Rippe, Karsten (Journal of cell science, 2010)
Promyelocytic leukemia nuclear bodies (PML-NBs) are mobile subnuclear organelles formed by PML and Sp100 protein. They have been reported to have a role in transcription, DNA replication and repair, telomere lengthening, cell cycle control and tumor suppression. We have conducted high-resolution 4Pi fluorescence laser-scanning microscopy studies complemented with correlative electron microscopy and investigations of the accessibility of the PML-NB subcompartment. During interphase PML-NBs adopt a spherical organization characterized by the assembly of PML and Sp100 proteins into patches within a 50- to 100-nm-thick shell. This spherical shell of PML and Sp100 imposes little constraint to the exchange of components between the PML-NB interior and the nucleoplasm. Post-translational SUMO modifications, telomere repeats and heterochromatin protein 1 were found to localize in characteristic patterns with respect to PML and Sp100. From our findings, we derived a model that explains how the three-dimensional organization of PML-NBs serves to concentrate different biological activities while allowing for an efficient exchange of components.